Writing a history of learning disabilities as Joey's dad. (21st February 2022) - Unwin, Stephen
Abstract: It is perhaps inevitable that the academic study of learning disabilities is often undertaken by established scholars with little lived experience of the condition. So, what has it been like for someone from outside the academy, with a long career in the arts, who is also the father of a severely learning‐disabled young man, to write a book‐length history of learning disabilities in culture and society? How is it possible to reconcile such a biological reality with the many caveats about the social construction of the condition? How can we retain a belief in scientific analysis when the categorisation of learning‐disabled people seems to have caused as many problems as it solves? Furthermore, how can such an account be attempted when so much of the written record is by people who are placed in positions of power over learning‐disabled people and when the true voice of experience is so often silenced, or, like the author's son, silent? The attempt to answer these questions reveals a field rich with contradiction. Despite some advances, much of the social and cultural history of learning disabilities tells a tale of neglect, abandonment and abuse, with confused cultural attitudes too often shaping practice. When the telescope is reversed, however, severe learning disabilities provide us with a kind of Brechtian "alienation effect" which reveals the fault lines running through so many progressive movements and helps us to frame them historically, while also challenging assumptions about how those with severe learning disabilities are regarded and can best be given the support and freedom that they need. Accessible summary: My son has severe learning disabilities and the experience of being his dad has changed my life. I am writing a book‐length history of learning disabilities to find out how changing attitudes have led to changing practice. I am not learning disabled. The history of learning‐disabled people is, for the most part, painful. We should not rely too much on the accounts of those in positions of power and draw on the small amount of history told by learning‐disabled people that exists. I explore how some of the most positive moments in history have been bad for learning‐disabled people. I explain how this can help us understand what we need to do if their lives are to be improved. I am interested in how learning‐disabled people have been represented in culture and society, and how this affects how they live.